Why Do You Trust Siri?: The Factors Affecting Trustworthiness of Intelligent Personal Assistant. Issue 1 (13th October 2021) - Wu, Dan; Huang, Yeman
Abstract: Trust greatly contributes to human‐AI collaboration, however, human's trust to IPA is hard to establish and lacks exploration. The purpose of this paper is to recognize the factors that affect the trustworthiness of IPA. 358 questionnaires were analyzed by PLS‐SEM to construct the model, while thematic analysis was used to discover expectance of IPA. Chi‐square tests and T‐test were used to distinguish the difference between two user groups. Three factors that capability of system, personality of agent, and availability of interface have a significant impact on the trustworthiness of IPA. The capability of system is the most essential as the threshold with users' plenty of expectations. Most users pay less attention to the availability of interface and the personality of agent has a great impact on the trustworthiness of IPA. The factors found enrich the trusted AI research and inspire insights of design of IPA.